Auditory-motor rhythm synchronization in children with autism spectrum disorder. (March 2017) - Tryfon, Ana; Foster, Nicholas E.; Ouimet, Tia; Doyle-Thomas, Krissy; Anagnostou, Evdokia; Sharda, Megha; Hyde, Krista L.; ,
Highlights: Auditory-motor rhythm synchronization was tested in ASD and TD children. ASD and TD children performed similarly across all rhythm complexities. ASD and TD children both performed worse with increasing complexity. ASD and TD children both performed better with age. This work helps better characterize auditory-motor interactions in ASD. Abstract: Background: Autism spectrum disorder (ASD) is characterized by difficulties in social and communication skills as well as atypical sensory perception and motor skills. Sensorimotor abilities such as auditory-motor integration are essential for social interaction and communication. The goal of this research was to investigate the development of auditory-motor rhythm synchronization for the first time in ASD versus typically-developing (TD) children. Methods: Participants were 31 boys with ASD and 23 TD boys that were matched in age and IQ. Participants were tested on an auditory-motor rhythm synchronization task in which they tapped in synchrony with rhythms of varying metrical complexity. Results: Both children with ASD and TD performed similarly on this task and both groups performed better with age. Conclusions: This work demonstrates that non-verbal rhythm synchronization is intact in ASD over the course of childhood development. This research serves to better understand sensorimotor interactions in ASD and to better define sensory phenotypes in ASD.